Profile of Laboratory Test Value in Confirmed COVID-19 Patients with Comorbid - Apriani, Apriani; Hwa, Fenny Ong Lian (Poltekkes Kemenkes Jakarta III, 2022)
Comorbid COVID-19 patients are a vulnerable group. This study aims to describe the characteristics of the laboratory values ​​of COVID-19 patients with comorbidities. This type of research is descriptive observational. The population and sample in this study were patients with confirmed COVID19 at the Siloam Hospital Lippo Village as many as 94 patients. Laboratory values ​​analyzed included Hemoglobin (Hb), Leukocytes (WBC), Platelets (PLT), D-dimer, Lactate dehydrogenase (LDH), C-reactive protein (CRP), and Procalcitonin (PCT). Respondent data and laboratory values ​​were analyzed descriptively, in the form of a summary of data for each variable. Respondent data, mostly in the age range of 50-59 years (33%) and male (53.2%). The most common comorbidities were hypertension (29.8%), Diabetes Mellitus and Chronis Cardiac Disease (16%), Chronic Obstructive Pulmonary and Chronic Kidney Disease (8.5%), Autoimmune and Cancer (10.6%) .The results of laboratory values ​​showed that the average values ​​of D-dimer (2.1 mg/mL), Lactate Dehydrogenase (418.45 mL), C-Reactive Protein (39.69 mg/L) and Procalcitonine (1.59 ng/mL) was increased in all comorbidities. Meanwhile, the examination values ​​of leukocytes, platelets and hemoglobin were in normal condition. The results of these laboratory tests can be used as prognostic predictors and risk of mortality in comorbid COVID-19 patients.